Teaching Grammar and Testing Grammar in the English Primary School: The Impact on Teachers and their Teaching of the Grammar Element of the Statutory Test in Spelling, Punctuation and Grammar (SPaG). Issue 1 (2nd January 2016) - Safford, Kimberly
Abstract: The research examined the impact on teachers of the grammar element of a new statutory test in Spelling, Punctuation and Grammar (SPaG) in primary schools in England. The research aimed to evaluate the nature and the extent of changes to the teaching of grammar and to wider literacy teaching since the introduction of the test in 2013. The research explored teachers' responses to teaching grammar to a statutory test format, and how teachers implemented rapid curriculum change in their classrooms. The research sought to learn the perspectives of teachers as they adjusted to new English assessments and new expectations for children's language in the primary school. This paper draws on teacher interviews ( n = 16) and an online survey of teaching staff ( n = 170). Teachers discuss their knowledge, understanding and enjoyment of grammar at their own level, and their skills for teaching pupils; they also discuss their observations of how pupils have responded to explicit grammar teaching and the grammar test. The data give some insights into the processes for teachers of applying new requirements for teaching and testing grammar, and how teachers strive to make grammar accessible to children. The findings discussed in this paper are: (1) since the introduction of the statutory SPaG test in primary schools, time spent teaching decontextualised and contextualised grammar has increased significantly; (2) grammar is now taught explicitly and formally as a classroom literacy routine; (3) the test format influences grammar teaching content and approaches; (4) teachers observe that pupils enjoy learning grammar and taking the test; (5) teachers disagree about the extent to which explicit grammar teaching and testing have a positive impact on pupils' language and literacy skills; (6) teachers feel more confident about teaching grammar.